A bismuth-doped zinc-based metal organic framework material and its preparation method and application

By using bismuth-doped zinc-based metal organic framework materials as catalysts, the existing electrocatalytic reduction CO2 catalysts have high cost, scarce resources and poor stability, and a low-cost, efficient and environmentally friendly CO2 reduction formic acid process is achieved.

CN115747845BActive Publication Date: 2025-04-22SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211360788.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-02
Publication Date
2025-04-22
Estimated Expiration
2042-11-02

AI Technical Summary

Technical Problem

The existing catalysts for electrocatalytic reduction of CO2 have problems such as high cost, scarce resources, and poor stability, making it difficult to achieve large-scale promotion and application.

Method used

Using bismuth-doped zinc-based metal organic framework material as a catalyst, a material with high specific surface area and excellent catalytic properties was prepared by dispersing bismuth salt, zinc salt and 2-methylimidazole in a solvent and adding amine compounds to react.

Benefits of technology

It has achieved low-cost, green and environmentally friendly, high-activity and high stability electrocatalytic reduction of CO2 to prepare formic acid, with excellent catalytic performance and is suitable for large-scale production applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115747845B_ABST
    Figure CN115747845B_ABST
Patent Text Reader

Abstract

The present invention discloses a bismuth-doped zinc-based metal organic framework material and a preparation method and application thereof. The preparation method of the bismuth-doped zinc-based metal organic framework material of the present invention comprises the following steps: dispersing a bismuth salt, a zinc salt and 2-methylimidazole in a solvent, adding an amine compound for reaction, and then separating a solid product to obtain a bismuth-doped zinc-based metal organic framework material. The bismuth-doped zinc-based metal organic framework material of the present invention has the advantages of large specific surface area, excellent catalytic performance for electrocatalytic reduction of CO2 to prepare formic acid, excellent stability, etc., and its preparation method is simple, the production cost is low, and it is safe and environmentally friendly, and is suitable for large-scale production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a bismuth-doped zinc-based metal organic framework material and a preparation method and application thereof. Background Art

[0002] Since the Industrial Revolution in the 19th century, with the over-exploitation and large-scale use of fossil fuels, the concentration of CO2 in the atmosphere has increased significantly, causing many environmental problems (such as global warming, melting glaciers, rising sea levels, etc.), and with the sharp increase in global energy demand, the consumption of non-renewable fossil fuels such as coal and oil on the earth is very fast. At the current consumption rate, people will face a serious energy crisis in the near future. Therefore, it is urgent to develop sustainable and environmentally friendly energy conversion technologies and to utilize CO2 as a resource.

[0003] The electrocatalytic reduction of CO2 to produce useful chemicals has the advantages of mild reaction conditions, simple operation, and easy control. It can also use renewable solar and wind energy to provide electricity, which is one of the effective ways to achieve CO2 conversion. However, the C=O bond in CO2 is very stable (the dissociation energy of C=O is 803kJ / mol), which is difficult to break, and a competitive water reduction hydrogen evolution reaction will occur during the electrocatalytic process. Therefore, an efficient catalyst is needed to promote the electroreduction process of CO2.

[0004] At present, the catalysts for the electrocatalytic reduction of CO2 can be divided into three categories according to the reduction products: 1) The first type of metal catalysts whose reduction products are formic acid or formate, including Sn, Bi, Hg, Pb and In, etc. Hg and Pb are very toxic, while Sn and In are easily dissolved in the electrolyte solution and have poor stability; 2) The second type of metal catalysts whose reduction products are CO, including Au, Ag, Zn and Pd, etc. This type of catalyst has high catalytic activity, but due to the scarcity of resources such as Au, Ag, Pd and high prices, its application is greatly limited; 3) The third type of metal catalyst Cu whose reduction products are multi-carbon compounds, although Cu can reduce CO2 to multi-carbon compounds, the selectivity of the product is poor. In summary, the catalysts currently used for the electrocatalytic reduction of CO2 have obvious defects and are difficult to promote and apply on a large scale.

[0005] Among the many products obtained by electrocatalytic reduction of CO2, formic acid has the advantages of diversified uses, high added value, and large market demand. Therefore, the electrochemical reduction of CO2 to prepare formic acid has broad development prospects.

[0006] Therefore, it is of great significance to develop a low-cost, green, environmentally friendly, highly active, highly stable catalyst suitable for the electrocatalytic reduction of CO2 to produce formic acid. Summary of the invention

[0007] The purpose of the present invention is to provide a bismuth-doped zinc-based metal organic framework material and a preparation method and application thereof.

[0008] The technical solution adopted by the present invention is:

[0009] A method for preparing a bismuth-doped zinc-based metal organic framework material comprises the following steps: dispersing a bismuth salt, a zinc salt and 2-methylimidazole in a solvent, adding an amine compound for reaction, and separating a solid product to obtain the bismuth-doped zinc-based metal organic framework material.

[0010] Preferably, a method for preparing a bismuth-doped zinc-based metal-organic framework material comprises the following steps: dispersing a bismuth salt and a zinc salt in a solvent, adding 2-methylimidazole pre-dispersed in the solvent, adding an amine compound to react, filtering, and drying the filtered solid product to obtain a bismuth-doped zinc-based metal-organic framework material.

[0011] Preferably, the molar ratio of the bismuth salt, the zinc salt and the 2-methylimidazole is 0.01-1:1:0.5-5.

[0012] More preferably, the molar ratio of the bismuth salt, the zinc salt and the 2-methylimidazole is 0.01-0.05:1:0.7-1.1.

[0013] Preferably, the molar ratio of the zinc salt to the amine compound is 1:1-10.

[0014] More preferably, the molar ratio of the zinc salt to the amine compound is 1:1-2.

[0015] Preferably, the bismuth salt is at least one of bismuth nitrate, bismuth sulfate, and ammonium bismuth citrate.

[0016] Preferably, the zinc salt is at least one of zinc nitrate, zinc sulfate and zinc chloride.

[0017] Preferably, the amine compound is at least one of triethylamine, N,N-dimethylformamide and diethanolamine.

[0018] Preferably, the solvent is at least one of methanol, ethanol and isopropanol.

[0019] Preferably, the reaction is carried out at room temperature (25°C±5°C) and the reaction time is 1 min to 30 min.

[0020] Preferably, the drying is carried out at 50°C to 70°C, and the drying time is 4h to 10h.

[0021] A bismuth-doped zinc-based metal organic framework material is prepared by the above preparation method.

[0022] A method for preparing formic acid by electrocatalytic reduction of CO2, wherein the catalyst used is the above-mentioned bismuth-doped zinc-based metal organic framework material.

[0023] The beneficial effects of the present invention are: the bismuth-doped zinc-based metal organic framework material of the present invention has the advantages of large specific surface area, excellent catalytic performance for electrocatalytic reduction of CO2 to produce formic acid, excellent stability, etc., and its preparation method is simple, the production cost is low, it is safe and environmentally friendly, and it is suitable for large-scale production applications.

[0024] Specifically:

[0025] 1) The bismuth-doped zinc-based metal organic framework material of the present invention has a large specific surface area, which can reach 1000m 2 / g or more;

[0026] 2) The bismuth-doped zinc-based metal organic framework material of the present invention has a uniform distribution of bismuth and can exhibit excellent stability when used in a CO2 electroreduction system;

[0027] 3) The bismuth-doped zinc-based metal organic framework material of the present invention can be used in a CO2 electroreduction system to exhibit excellent formic acid Faradaic efficiency. At a potential of -2.0 V vs. Ag / AgCl, the formic acid Faradaic efficiency is as high as 97.5%;

[0028] 4) The preparation method of the bismuth-doped zinc-based metal organic framework material of the present invention is fast, simple and easy, the raw materials are widely available and inexpensive, the equipment requirements are low, the preparation process is controllable and environmentally friendly, no strong acid or strong base is generated, it is easy to achieve large-scale preparation of the product, and the application prospects are broad. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 These are SEM images of the bismuth-doped zinc-based metal organic framework materials of Examples 1 to 4.

[0030] Figure 2 The XRD diagrams of the bismuth-doped zinc-based metal organic framework materials of Examples 1 to 4 and the zinc-based metal organic framework material of Comparative Example 1 are shown.

[0031] Figure 3 Isothermal nitrogen absorption-desorption curves of the bismuth-doped zinc-based metal organic framework materials of Examples 1-4.

[0032] Figure 4 This is an elemental surface scanning spectrum of the bismuth-doped zinc-based metal organic framework material of Example 2.

[0033] Figure 5 This is the XRD pattern of the bismuth-doped zinc-based metal organic framework material of Example 5.

[0034] Figure 61 is the XRD diagram of the bismuth-doped zinc-based metal organic framework material of Examples 6 to 7.

[0035] Figure 7 This is the XPS graph of the bismuth-doped zinc-based metal organic framework material of Example 6.

[0036] Figure 8 This is a local XRD pattern of the bismuth-doped zinc-based metal organic framework material of Example 7.

[0037] Fig. 9 1 and 2 are XRD diagrams of the bismuth-doped zinc-based metal organic framework materials of Examples 8 to 11.

[0038] Fig.10 This is the SEM image of the zinc-based metal organic framework material of Comparative Example 1.

[0039] Fig.11 This is the isothermal nitrogen absorption-desorption curve of the zinc-based metal organic framework material of Comparative Example 1.

[0040] Fig.12 The performance diagram of the bismuth-doped zinc-based metal organic framework materials of Examples 1 to 4 for electrocatalytic reduction of CO2 at different potentials.

[0041] Fig.13 This is a performance diagram of the zinc-based metal organic framework material of comparative example 1 for electrocatalytic reduction of CO2 at different potentials.

[0042] Fig.14 The performance diagram of the bismuth-doped zinc-based metal organic framework materials of Example 2 and Examples 5 to 7 for the electrocatalytic reduction of CO2 at different potentials.

[0043] Fig.15 This is a graph showing the stability test results of the bismuth-doped zinc-based metal organic framework material of Example 6 for the electrocatalytic reduction of CO2 under constant potential conditions. DETAILED DESCRIPTION

[0044] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0045] Embodiment 1:

[0046] A bismuth-doped zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0047] 0.026 g (0.054 mmol) of bismuth nitrate and 0.67 g (2.25 mmol) of zinc nitrate were dispersed in 20 mL of methanol, and 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of diethanolamine was added. The reaction was carried out at room temperature for 1 min, and the filtered solid product was placed in a vacuum oven at 60 ° C and dried for 6 h to obtain a bismuth-doped zinc-based metal organic framework material (white powder, recorded as sample 1).

[0048] The scanning electron microscope (SEM) image of the bismuth-doped zinc-based metal organic framework material (sample 1) of this example is as follows: Figure 1 As shown, the X-ray diffraction (XRD) pattern is as follows Figure 2 As shown in the figure, the isothermal nitrogen adsorption-desorption curve is as follows Figure 3 shown.

[0049] Depend on Figure 1 It can be seen that the bismuth-doped zinc-based metal organic framework material of this embodiment is composed of nanoparticles with a spherical structure, and the particle size of the nanoparticles is 50nm to 100nm.

[0050] Depend on Figure 2 It can be seen that the diffraction peak position of the bismuth-doped zinc-based metal organic framework material in this embodiment is consistent with the single crystal simulated ZIF-8 (ZIF-8 metal organic framework), and there are no other diffraction peaks, indicating that diethanolamine is used as a deprotonating agent and template agent to successfully prepare a material with a typical ZIF-8 type topological structure at room temperature.

[0051] Depend on Figure 3 It can be seen that under low pressure (P / P0<0.1), the isothermal nitrogen adsorption-desorption curve increases sharply, which is a typical type IV isotherm. After testing, the specific surface area of ​​the bismuth-doped zinc-based metal organic framework material of this embodiment is as high as 1021.9m 2 / g.

[0052] Embodiment 2:

[0053] A bismuth-doped zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0054] 0.026 g (0.054 mmol) of bismuth nitrate and 0.67 g (2.25 mmol) of zinc nitrate were dispersed in 20 mL of methanol, and 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of diethanolamine was added. The reaction was carried out at room temperature for 5 minutes, and the filtered solid product was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a bismuth-doped zinc-based metal organic framework material (white powder, recorded as sample 2).

[0055] The SEM image of the bismuth-doped zinc-based metal organic framework material (sample 2) of this example is as follows: Figure 1 As shown, the XRD pattern is Figure 2 As shown in the figure, the isothermal nitrogen adsorption-desorption curve is as follows Figure 3 As shown, the element surface scanning spectrum is as follows Figure 4 (a is the electron image, b is the BiMα1 image, and c is the surface spectrum).

[0056] Depend on Figure 1 and Figure 4 It can be seen that the bismuth-doped zinc-based metal organic framework material of this embodiment is composed of nanoparticles with a spherical structure, the particle size of the nanoparticles is 50nm-100nm, and the bismuth is evenly distributed in the entire sample.

[0057] Depend on Figure 2 It can be seen that the diffraction peak position of the bismuth-doped zinc-based metal organic framework material in this embodiment is consistent with the single crystal simulated ZIF-8, and there are no other diffraction peaks, indicating that diethanolamine is used as a deprotonating agent and template agent to successfully prepare a material with a typical ZIF-8 type topological structure at room temperature.

[0058] Depend on Figure 3 It can be seen that under low pressure (P / P0<0.1), the isothermal nitrogen adsorption-desorption curve increases sharply, which is a typical type IV isotherm. After testing, the specific surface area of ​​the bismuth-doped zinc-based metal organic framework material of this embodiment is as high as 1011.3m 2 / g.

[0059] Embodiment 3:

[0060] A bismuth-doped zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0061] 0.026 g (0.054 mmol) of bismuth nitrate and 0.67 g (2.25 mmol) of zinc nitrate were dispersed in 20 mL of methanol, and 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of diethanolamine was added. The reaction was carried out at room temperature for 10 min, and the filtered solid product was placed in a vacuum oven at 60 ° C and dried for 6 h to obtain a bismuth-doped zinc-based metal organic framework material (white powder, recorded as sample 3).

[0062] The SEM image of the bismuth-doped zinc-based metal organic framework material (sample 3) of this example is as follows: Figure 1 As shown, the XRD pattern is Figure 2 As shown in the figure, the isothermal nitrogen adsorption-desorption curve is as follows Figure 3 shown.

[0063] Depend on Figure 1It can be seen that the bismuth-doped zinc-based metal organic framework material of this embodiment is composed of nanoparticles with a spherical structure, and the particle size of the nanoparticles is 50nm to 100nm.

[0064] Depend on Figure 2 It can be seen that the diffraction peak position of the bismuth-doped zinc-based metal organic framework material in this embodiment is consistent with the single crystal simulated ZIF-8, and there are no other diffraction peaks, indicating that diethanolamine is used as a deprotonating agent and template agent to successfully prepare a material with a typical ZIF-8 type topological structure at room temperature.

[0065] Depend on Figure 3 It can be seen that under low pressure (P / P0<0.1), the isothermal nitrogen adsorption-desorption curve increases sharply, which is a typical type IV isotherm. After testing, the specific surface area of ​​the bismuth-doped zinc-based metal organic framework material of this embodiment is as high as 922.8 m 2 / g.

[0066] Embodiment 4:

[0067] A bismuth-doped zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0068] 0.026 g (0.054 mmol) of bismuth nitrate and 0.67 g (2.25 mmol) of zinc nitrate were dispersed in 20 mL of methanol, and 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of diethanolamine was added. The reaction was carried out at room temperature for 30 min, and the filtered solid product was placed in a vacuum oven at 60 ° C and dried for 6 h to obtain a bismuth-doped zinc-based metal organic framework material (white powder, recorded as sample 4).

[0069] The SEM image of the bismuth-doped zinc-based metal organic framework material (sample 4) of this example is as follows: Figure 1 As shown, the XRD pattern is Figure 2 As shown in the figure, the isothermal nitrogen adsorption-desorption curve is as follows Figure 3 shown.

[0070] Depend on Figure 1 It can be seen that the bismuth-doped zinc-based metal organic framework material of this embodiment is composed of nanoparticles with a spherical structure, and the particle size of the nanoparticles is 50nm to 100nm.

[0071] Depend on Figure 2 It can be seen that the diffraction peak position of the bismuth-doped zinc-based metal organic framework material in this embodiment is consistent with the single crystal simulated ZIF-8, and there are no other diffraction peaks, indicating that diethanolamine is used as a deprotonating agent and template agent to successfully prepare a material with a typical ZIF-8 type topological structure at room temperature.

[0072] Depend on Figure 3It can be seen that under low pressure (P / P0<0.1), the isothermal nitrogen adsorption-desorption curve increases sharply, which is a typical type IV isotherm. After testing, the specific surface area of ​​the bismuth-doped zinc-based metal organic framework material of this embodiment is as high as 998.7 m 2 / g.

[0073] Embodiment 5:

[0074] A bismuth-doped zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0075] 0.013 g (0.027 mmol) of bismuth nitrate and 0.67 g (2.25 mmol) of zinc nitrate were dispersed in 20 mL of methanol, and 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of diethanolamine was added. The reaction was carried out at room temperature for 5 min, and the filtered solid product was placed in a vacuum oven at 60 ° C and dried for 6 h to obtain a bismuth-doped zinc-based metal organic framework material (white powder, recorded as sample 5).

[0076] The XRD pattern of the bismuth-doped zinc-based metal organic framework material (sample 5) of this example is as follows: Figure 5 shown.

[0077] Depend on Figure 5 It can be seen that the diffraction peak position of the bismuth-doped zinc-based metal organic framework material in this embodiment is consistent with the single crystal simulated ZIF-8, and there are no other diffraction peaks, indicating that diethanolamine is used as a deprotonating agent and template agent to successfully prepare a material with a typical ZIF-8 type topological structure at room temperature.

[0078] Embodiment 6:

[0079] A bismuth-doped zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0080] 0.039 g (0.080 mmol) of bismuth nitrate and 0.67 g (2.25 mmol) of zinc nitrate were dispersed in 20 mL of methanol, and 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of diethanolamine was added. The reaction was carried out at room temperature for 5 min, and the filtered solid product was placed in a vacuum oven at 60 ° C and dried for 6 h to obtain a bismuth-doped zinc-based metal organic framework material (white powder, recorded as sample 6).

[0081] The XRD pattern of the bismuth-doped zinc-based metal organic framework material (sample 6) of this example is as follows: Figure 6 As shown in the XPS diagram Figure 7 shown.

[0082] Depend on Figure 6It can be seen that the diffraction peak position of the bismuth-doped zinc-based metal organic framework material of this embodiment is consistent with the single crystal simulated ZIF-8, and diffraction peaks with smaller intensity appear at 27.95°, 32.38° and 46.45°, which are consistent with the X-ray diffraction standard card of bismuth oxide (PDF#27-0052), indicating that diethanolamine is used as a deprotonating agent and template agent to successfully prepare a bismuth-doped material with a typical ZIF-8 type topological structure at room temperature, and the diffraction peak of bismuth oxide will appear when the amount of Bi is large.

[0083] Depend on Figure 7 It can be seen that Bi 4f is fitted into two peaks, namely 4f at 158.38 eV 5 / 2 and 4f at 163.68 eV 7 / 2 , indicating that the bismuth in the bismuth-doped zinc-based metal organic framework material of this embodiment exists in a positive trivalent form.

[0084] Embodiment 7:

[0085] A bismuth-doped zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0086] 0.052 g (0.107 mmol) of bismuth nitrate and 0.67 g (2.25 mmol) of zinc nitrate were dispersed in 20 mL of methanol, and 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of diethanolamine was added. The reaction was carried out at room temperature for 5 minutes, and the filtered solid product was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a bismuth-doped zinc-based metal organic framework material (white powder, recorded as sample 7).

[0087] The XRD pattern of the bismuth-doped zinc-based metal organic framework material (sample 7) of this example is as follows: Figure 6 As shown, the local XRD pattern (compared with the standard PDF card of bismuth oxide) is as follows Figure 8 shown.

[0088] Depend on Figure 6 and Figure 8 It can be seen that the diffraction peak position of the bismuth-doped zinc-based metal organic framework material of this embodiment is consistent with the single crystal simulated ZIF-8, and diffraction peaks with smaller intensity appear at 27.95°, 32.38° and 46.45°, which are consistent with the X-ray diffraction standard card of bismuth oxide (PDF#27-0052), indicating that diethanolamine is used as a template to successfully prepare a bismuth-doped material with a typical ZIF-8 type topological structure at room temperature, and the diffraction peak of bismuth oxide will appear when the amount of Bi is large.

[0089] Embodiment 8:

[0090] A bismuth-doped zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0091] 0.052 g (0.107 mmol) of bismuth nitrate and 0.67 g (2.25 mmol) of zinc nitrate were dispersed in 20 mL of methanol, and 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of N,N-dimethylformamide was added. The reaction was carried out at room temperature for 5 min, and the filtered solid product was placed in a vacuum oven at 60 ° C and dried for 6 h to obtain a bismuth-doped zinc-based metal organic framework material (white powder, recorded as sample 8).

[0092] The XRD pattern of the bismuth-doped zinc-based metal organic framework material (sample 8) of this example is as follows: Fig. 9 shown.

[0093] Depend on Fig. 9 It can be seen that the diffraction peak position of the bismuth-doped zinc-based metal organic framework material of this embodiment is consistent with the single crystal simulated ZIF-8, indicating that a material with a typical ZIF-8 type topological structure was successfully prepared at room temperature using N,N-dimethylformamide as a deprotonating agent and template agent.

[0094] Embodiment 9:

[0095] A bismuth-doped zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0096] 0.052 g (0.107 mmol) of bismuth nitrate and 0.67 g (2.25 mmol) of zinc nitrate were dispersed in 20 mL of methanol, and 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of triethylamine was added. The reaction was carried out at room temperature for 5 min, and the filtered solid product was placed in a vacuum oven at 60 ° C and dried for 6 h to obtain a bismuth-doped zinc-based metal organic framework material (white powder, recorded as sample 9).

[0097] The XRD pattern of the bismuth-doped zinc-based metal organic framework material (sample 9) of this example is as follows: Fig. 9 shown.

[0098] Depend on Fig. 9 It can be seen that the diffraction peak position of the bismuth-doped zinc-based metal organic framework material of this embodiment is consistent with the single crystal simulated ZIF-8, indicating that a material with a typical ZIF-8 type topological structure was successfully prepared at room temperature using triethylamine as a deprotonating agent and template agent.

[0099] Embodiment 10:

[0100] A bismuth-doped zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0101] 0.048 g (0.107 mmol) of ammonium bismuth citrate and 0.67 g (2.25 mmol) of zinc nitrate were dispersed in 20 mL of methanol, and 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of diethanolamine was added. The reaction was carried out at room temperature for 5 minutes, and the filtered solid product was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a bismuth-doped zinc-based metal organic framework material (white powder, recorded as sample 10).

[0102] The XRD pattern of the bismuth-doped zinc-based metal organic framework material (sample 10) of this embodiment is as follows: Fig. 9 shown.

[0103] Depend on Fig. 9 It can be seen that the diffraction peak position of the bismuth-doped zinc-based metal organic framework material of this embodiment is consistent with the single crystal simulated ZIF-8, indicating that a material with a typical ZIF-8 type topological structure was successfully prepared at room temperature using diethanolamine as a deprotonating agent and template agent.

[0104] Embodiment 11:

[0105] A bismuth-doped zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0106] 0.052 g (0.107 mmol) of bismuth nitrate and 0.85 g (2.25 mmol) of zinc sulfate were dispersed in 20 mL of methanol, and 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of diethanolamine was added. The reaction was carried out at room temperature for 5 minutes, and the filtered solid product was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a bismuth-doped zinc-based metal organic framework material (white powder, recorded as sample 11).

[0107] The XRD pattern of the bismuth-doped zinc-based metal organic framework material (sample 11) of this embodiment is as follows: Fig. 9 shown.

[0108] Depend on Fig. 9 It can be seen that the diffraction peak position of the bismuth-doped zinc-based metal organic framework material of this embodiment is consistent with the single crystal simulated ZIF-8, indicating that a material with a typical ZIF-8 type topological structure was successfully prepared at room temperature using diethanolamine as a deprotonating agent and template agent.

[0109] Comparative Example 1:

[0110] A zinc-based metal organic framework material, the preparation method of which comprises the following steps:

[0111] 0.67 g (2.25 mmol) of zinc nitrate was dispersed in 20 mL of methanol, and then 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of diethanolamine was added. The reaction was carried out at room temperature for 5 min, and the filtered solid product was placed in a vacuum oven at 60 ° C and dried for 6 h to obtain a zinc-based metal organic framework material (white powder, recorded as comparative sample 1).

[0112] The XRD pattern of the zinc-based metal organic framework material (comparative sample 1) of this comparative example is as follows: Figure 2 As shown in the SEM images Fig.10 As shown in the figure, the isothermal nitrogen adsorption-desorption curve is as follows Fig.11 shown.

[0113] Depend on Figure 2 It can be seen that the diffraction peak position of the zinc-based metal organic framework material in this comparative example is consistent with the single crystal simulated ZIF-8, indicating that a material with a typical ZIF-8 type topological structure was successfully prepared at room temperature using diethanolamine as a deprotonating agent and template agent.

[0114] Depend on Fig.10 It can be seen that the zinc-based metal organic framework material of this comparative example is composed of nanoparticles with a spherical structure, and the particle size of the nanoparticles is 50nm to 100nm.

[0115] Depend on Fig.11 It can be seen that under low pressure (P / P0<0.1), the isothermal nitrogen adsorption-desorption curve increases sharply, which is a typical type IV isotherm. After testing, the specific surface area of ​​the zinc-based metal organic framework material in this comparative example is as high as 1320.7m 2 / g.

[0116] Comparative Example 2:

[0117] 0.052 g (0.107 mmol) of bismuth nitrate was dispersed in 20 mL of methanol, and then 0.167 g (2 mmol) of 2-methylimidazole pre-dispersed in 20 mL of methanol was added, and then 3 mmol of diethanolamine was added. The reaction was carried out at room temperature for 5 minutes. The reaction solution was white and transparent, and no precipitation was generated.

[0118] In summary, there is no coordination between bismuth ions and 2-methylimidazole between bismuth salt and 2-methylimidazole, thus failing to form a metal organic framework material.

[0119] Electrocatalytic performance test:

[0120] 1) Take 5 mg of the bismuth-doped zinc-based metal organic framework material of Examples 1 to 4 and the zinc-based metal organic framework material of Comparative Example 1 to prepare catalyst ink, then coat it on hydrophobic carbon paper, dry it, use it as a working electrode, a platinum sheet as a counter electrode, an Ag / AgCl electrode as a reference electrode, and an electrolyte of 0.1 mol / L KHCO3 solution (CO2 is already saturated). Perform a CO2 electroreduction test in an H-type electrolytic cell, and the performance diagram of electrocatalytic CO2 reduction at different potentials is as shown in the figure. Fig.12 and 13 shown.

[0121] Depend on Fig.12 and Fig.13 It can be seen that for the bismuth-doped zinc-based metal-organic framework materials of Examples 1 to 4, the optimal Faraday efficiency of the product formic acid is higher than 90%, while for the zinc-based metal-organic framework material of Comparative Example 1, hydrogen evolution is the main reaction within the measured potential range, indicating that bismuth doping greatly improves the selectivity of ZIF-8 electrocatalytic reduction of CO2 to produce formic acid.

[0122] 2) Take 5 mg of the bismuth-doped zinc-based metal organic framework material of Example 2 and Examples 5 to 7 respectively to prepare a catalyst ink, then coat it on a hydrophobic carbon paper, dry it, use it as a working electrode, a platinum sheet as a counter electrode, an Ag / AgCl electrode as a reference electrode, and an electrolyte of 0.1 mol / L KHCO3 solution (CO2 is already saturated). Perform a CO2 electroreduction test in an H-type electrolytic cell, and the performance diagram of electrocatalytic CO2 reduction at different potentials is as shown in the figure. Fig.14 shown.

[0123] Depend on Fig.14 It can be seen that the bismuth-doped zinc-based metal organic framework material of Example 6 has the best performance. At -2.0 V (vs. Ag / AgCl), the corresponding formic acid Faraday efficiency is as high as 97.5%.

[0124] 3) Take 5 mg of the bismuth-doped zinc-based metal organic framework material of Example 6 to prepare a catalyst ink, then coat it on a hydrophobic carbon paper, dry it, use it as a working electrode, a platinum sheet as a counter electrode, an Ag / AgCl electrode as a reference electrode, and an electrolyte of 0.1 mol / L KHCO3 solution (CO2 is already saturated). A constant potential (-2.0 V vs. Ag / AgCl) CO2 electroreduction stability test is performed in an H-type electrolytic cell. The stability test results are shown in the figure below. Fig.15 shown.

[0125] Depend on Fig.15 It can be seen that in the stability test of the bismuth-doped zinc-based metal organic framework material of Example 6 for 11 hours, the current did not decay, and the Faradaic efficiency (FE COand FE H2 ) are all below 10%, indicating that the bismuth-doped zinc-based metal organic framework material of the present invention has excellent stability.

[0126] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing formic acid by electrocatalytic reduction of CO2, characterized in that: The catalyst used is a bismuth-doped zinc-based metal organic framework material; the bismuth-doped zinc-based metal organic framework material is prepared by a preparation method comprising the following steps: dispersing a bismuth salt, a zinc salt and 2-methylimidazole in a solvent, adding an amine compound for reaction, and separating a solid product to obtain the bismuth-doped zinc-based metal organic framework material.

2. The method for preparing formic acid by electrocatalytic reduction of CO2 according to claim 1, characterized in that: The molar ratio of the bismuth salt, the zinc salt and the 2-methylimidazole is 0.01-1:1:0.5-5.

3. The method for preparing formic acid by electrocatalytic reduction of CO2 according to claim 1 or 2, characterized in that: The molar ratio of the zinc salt to the amine compound is 1:1-10.

4. The method for preparing formic acid by electrocatalytic reduction of CO2 according to claim 1 or 2, characterized in that: The bismuth salt is at least one of bismuth nitrate, bismuth sulfate and ammonium bismuth citrate.

5. The method for preparing formic acid by electrocatalytic reduction of CO2 according to claim 1 or 2, characterized in that: The zinc salt is at least one of zinc nitrate, zinc sulfate and zinc chloride.

6. The method for preparing formic acid by electrocatalytic reduction of CO2 according to claim 1 or 2, characterized in that: The amine compound is at least one of triethylamine, N,N-dimethylformamide and diethanolamine.

7. The method for preparing formic acid by electrocatalytic reduction of CO2 according to claim 1 or 2, characterized in that: The solvent is at least one of methanol, ethanol and isopropanol.

8. The method for preparing formic acid by electrocatalytic reduction of CO2 according to claim 1 or 2, characterized in that: The reaction is carried out at room temperature, and the reaction time is 1 min to 30 min.

Citation Information

Patent Citations

  • Preparation method of cobalt-based metal organic framework derivative catalyst for catalytic decomposition of N2O

    CN112138725A

  • Preparation method of Bi-NC catalyst for carbon dioxide electroreduction

    CN112853378A